STRATEGI OPTIMALISASI MANAJEMEN PENGELOLAAN KJKS BMT AL MARKAZ AL ISLAMI MAKASSAR - Muhlis Damirah (UIN Mataram, 2019)
This article about application and strategy to management optimize of the KJKS BMTAl Markaz Al Islami Makassar. The method used in the implementation research is touse a qualitative descriptive approach. The results research study explained the fact isnot all Makassar society can obtain loan financing in banks. Often because of theinability to meet the requirements and administrative requirements must be met. Thepresence of the KJKS BMT Al Markaz Al Islami Makassar as an alternative effort tofind solutions in protecting the community, facilitating limitations and capital needs.Through the Management optimization strategy, the management of the institution isable to survive and maintain, in the midst of the community who need capital assistanceand experience limitations in business as a source to respond to public unrest inapplying for loans or additional business capital without being burdened withtroublesome interest. Besides acting as a business institution, also carries humanitarianmissions form of social and da'wah in the Makassar community.